162k views
2 votes
Simplify the complex expression and show work

Simplify the complex expression and show work-example-1

1 Answer

2 votes

The answer is


(-9+3√(2))+(3√(2)-2)i

=======================================================

Work Shown:


(-3+√(-2))(3-√(2))


(-3+√(-1*2))(3-√(2))


(-3+√(-1)*√(2))(3-√(2))


(-3+i√(2))(3-√(2))


x(3-√(2)) let
x=-3+i√(2)


3x-x*√(2) distribute


3(x)-√(2)(x)


3(-3+i√(2))-√(2)(-3+i√(2))


-9+3i√(2)+3√(2)-i*√(2)*√(2)


-9+3i√(2)+3√(2)-2i


-9+3√(2)+3i√(2)-2i


(-9+3√(2))+(3√(2)-2)i

The use of parenthesis in the last step is to help separate out the terms.

The last expression shown above is in the form a+bi where


a=-9+3√(2)


b=3√(2)-2

User Rosalynn
by
4.9k points